2016
DOI: 10.1002/cyto.b.21482
|View full text |Cite
|
Sign up to set email alerts
|

A novel flow cytometric assay for detection of residual disease in patients with B‐lymphoblastic leukemia/lymphoma post anti‐CD19 therapy

Abstract: These preliminary findings describe a strategy that performs well for residual disease detection in B-LL post anti-CD19 therapy. Such alternative strategies will become more important as the use of targeted immunotherapies becomes more common. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 23 publications
(35 reference statements)
4
112
0
3
Order By: Relevance
“…Although alternative gating strategies can be applied (eg, based on CD10, CD34, and/or CD45), one could also decide to add CD24 and/or CD22 to the current tubes (transforming it into a 10-color tube) in MRD-based trials involving Blinatumomab. 43 Addition of CD24 and CD22 will also have the advantage that the earliest BCP cells, expressing CD24 and/or CD22 but not yet CD19, 44 can be identified; this may be of relevance for the identification of all BCP cells in regenerating BM samples.…”
Section: Discussionmentioning
confidence: 99%
“…Although alternative gating strategies can be applied (eg, based on CD10, CD34, and/or CD45), one could also decide to add CD24 and/or CD22 to the current tubes (transforming it into a 10-color tube) in MRD-based trials involving Blinatumomab. 43 Addition of CD24 and CD22 will also have the advantage that the earliest BCP cells, expressing CD24 and/or CD22 but not yet CD19, 44 can be identified; this may be of relevance for the identification of all BCP cells in regenerating BM samples.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of B-ALL diagnostic IP vs. relapse IP showed that CD19 is most stable, while CD34 and CD20 differ significantly in nearly half of the cases (31). Utilization of CD22 and CD24, according the method of Cherian et al is a useful approach for MRD detection of CD19 negative/silent disease (15). In our study, we observed a slight down-regulation of CD19 and CD20 at relapse after the second CAR-T cell infusion in Patient 5.…”
Section: Discussionmentioning
confidence: 99%
“…PB and BM were collected pre-and post-CAR-T, and processed for 8-color FCM within 24 h of collection with cocktailed antibodies (see Supporting information), based on Children's Oncology Group guidelines (14), and modification of the Cherian et al approach (15). FCM procedure (16) included NH 4 Cl whole blood lysis, phosphate-buffered saline wash and antibody incubation.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Immunotherapy has also been associated with decreased expression of non-targeted antigens, such as decreased CD19 following anti-CD20 monoclonal antibody therapy, decreased CD19, CD21, and CD79a by trogocytosis following anti-CD22 therapy (68) and decreased CD20 during therapy with the B-cell receptor inhibitor ibrutinib (69). It is also essential to consider post-treatment changes during panel design for MRD detection (63), and demonstrate that the selected antibody combination meets desired assay performance characteristics through appropriate validation studies (70,71). It is recommended that panels include antibodies to several lineage-associated antigens and a gating strategy is adopted that accounts for all events and highlights antigen negative cells (70) (Fig.…”
Section: Role Of Flow Cytometry In Therapeutic Decisionmentioning
confidence: 99%